World Saldidae: Supplement (1987–2018) to the catalog and bibliography of the Leptopodomorpha (Heteroptera) - Larivière, Marie-Claude; Larochelle, André (Zootaxa, 2019)
A supplement to the Saldidae section of the “Catalog and bibliography of the Leptopodomorpha (Heteroptera)” published by Schuh, Galil and Polhemus (1987: Bull. Amer. Mus. Nat. Hist. 323), is provided. A total of 30 genera and 307 species-group taxa (298 species, 9 subspecies) belonging to 3 tribes and 2 subfamilies of extant Saldidae, is recorded for the world. Changes to the 1987 catalogue are documented. The synonymy and type locality of taxa described between 1987 and 2018 are given. Under each genus, species, and subspecies, geographic distribution is broadly categorised following the terrestrial zoogeographic realms of Holt et al. (2013: Science 339). A summary of the geographic distribution of Saldidae genera is provided as well as faunistic lists of species-group taxa by zoogeographic realms.